2016
DOI: 10.1120/jacmp.v17i6.6408
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive evaluation of adaptive daily planning for cervical cancer HDR brachytherapy

Abstract: The purpose of this study was to evaluate adaptive daily planning for cervical cancer patients who underwent high‐dose‐rate intracavitary brachytherapy (HDR‐BT) using comprehensive interfractional organ motion measurements. This study included 22 cervical cancer patients who underwent 5 fractions of HDR‐BT. Regions of interest (ROIs) including high‐risk clinical tumor volume (HR‐CTV) and organs at risk (OARs) were manually contoured on daily CT images. All patients were clinically treated with adaptive daily p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…When available, and following commissioning, use of 3D applicator models is recommended. If available, verification imaging is recommended when a patient transfer is required as part of the treatment workflow to account for potential patient movement or disturbance of the applicator(s). The dosimetric significance of this potential motion remains controversial, and is dependent on the type of implant (e.g., intracavitary versus interstitial), sedation, and the immobilization equipment utilized 185–188 . For instance, motion can be minimized with tighter packing although this may require the administration of anesthesia. Develop a plan with an MRI physicist and/or vendor to ensure SAR limits are not exceeded in special situations such as when a patient is anesthetized/sedated or has an implanted device. Work with an MRI physicist and /or vendor to develop a QA program for the MRI scanner (e.g., image quality, image geometry, image transfer integrity, orientation).…”
Section: Recommendations To the Medical Physicistsmentioning
confidence: 99%
“…When available, and following commissioning, use of 3D applicator models is recommended. If available, verification imaging is recommended when a patient transfer is required as part of the treatment workflow to account for potential patient movement or disturbance of the applicator(s). The dosimetric significance of this potential motion remains controversial, and is dependent on the type of implant (e.g., intracavitary versus interstitial), sedation, and the immobilization equipment utilized 185–188 . For instance, motion can be minimized with tighter packing although this may require the administration of anesthesia. Develop a plan with an MRI physicist and/or vendor to ensure SAR limits are not exceeded in special situations such as when a patient is anesthetized/sedated or has an implanted device. Work with an MRI physicist and /or vendor to develop a QA program for the MRI scanner (e.g., image quality, image geometry, image transfer integrity, orientation).…”
Section: Recommendations To the Medical Physicistsmentioning
confidence: 99%
“…In general, not only the volumes of the targets and OARs, but also the topography change. Meerschaert et al evaluated the similarity between fraction 1 and fractions 2-5 for HR-CTV and OARs in 22 cervical cancer patients who received 5 fractions of HDR brachytherapy (35). The results showed that the mean Dice similarity coefficient values of the HR-CTV, bladder, rectum, and sigmoid were 0.4-0.5, 0.6-0.7, 0.5, and 0.3-0.4, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The incorporation of applicator displacement worst-case scenarios into the robust optimization with the use of a MAD function may enable the robust optimization approach to minimize the dose delivery uncertainty in a single plan approach for HDR brachytherapy treatment planning. Meerschaert et al [55] found the importance of adaptive planning method for cervical cancer HDR brachytherapy; however, a simulation device is not routinely available in some institution. Hence, a robust optimization method with a multi-objective genetic algorithm in a single plan approach for minimizing dose delivery uncertainty by potential applicator displacements was proposed.…”
Section: Discussionmentioning
confidence: 99%